2004
DOI: 10.1016/s0969-6989(03)00051-1
|View full text |Cite
|
Sign up to set email alerts
|

Consumer evaluations of store brands: effects of store image and product attributes

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
270
4
20

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(307 citation statements)
references
References 44 publications
13
270
4
20
Order By: Relevance
“…Dessa forma, melhorar a qualidade dos produtos de marcas próprias, diminuir a variação da qualidade dentro das categorias e criar uma boa relação entre custo e benefício, conforme sugerido por Semeijn et al (2004) …”
Section: Avaliação Das Hipóteses E Discussão Dos Resultadosunclassified
See 2 more Smart Citations
“…Dessa forma, melhorar a qualidade dos produtos de marcas próprias, diminuir a variação da qualidade dentro das categorias e criar uma boa relação entre custo e benefício, conforme sugerido por Semeijn et al (2004) …”
Section: Avaliação Das Hipóteses E Discussão Dos Resultadosunclassified
“…Para Richardson, Dick, e Jain (1996), a imagem da loja tem efeito positivo na atitude em relação aos produtos de marcas próprias, funcionando como um combustível para a atitude do consumidor em relação à marca própria do varejista, e é um importante preditor da atitude em relação a essas marcas (Semeijn et al, 2004). A imagem da loja tem efeito positivo e direto na avaliação do consumidor em relação às marcas próprias (Liljander et al, 2009;Semeijn et al, 2004).…”
Section: Imagem Da Loja E Marca Própriaunclassified
See 1 more Smart Citation
“…As prior research suggests, both store image and product signature induce positive evaluations on consumers . Additionally, according to Semeijn, Riel, and Ambrosini (2004), store image acts as a risk reliever and positively influences consumers' evaluations of storebranded products. Consequently, the presence of a manufacturer signature or identification on a store brand product creates a strong association or link between the product manufacturer and the store brand, reducing purchase risk .…”
Section: Conceptual Framework Store Brands' Positioning and Manufactumentioning
confidence: 99%
“…Research in other categories has shown that the store name mitigates consumers' perceived risk of buying a brand (Agarwal and Teas, 2001) and that intentions to purchase private label products are influenced by consumers' perceptions of the retailer's capability of producing the product (DelVecchio, 2001;Semeijn et al, 2004). Retailers' own brands are generally associated with higher perceived risk levels than corresponding national brands.…”
Section: 3mentioning
confidence: 99%